Let’s Talk About BiTEs and Other Drugs in the Real-Life Setting for B-Cell Acute Lymphoblastic Leukemia - Deak, Dalma; Pop, Cristina; Zimta, Alina-Andreea; Jurj, Ancuta; Ghiaur, Alexandra; Pasca, Sergiu; Teodorescu, Patric; Dascalescu, Angela; Antohe, Ion; Ionescu, Bogdan; Constantinescu, Catalin; Onaciu, Anca; et al. (Frontiers in Immunology, 2019)
Background. Therapy for acute lymphoblastic leukemia (ALL) are currently initially efficient, but even if a high percentage of patients have an initial complete remission (CR), most of them relapse. Recent data shows that immunotherapy with either bispecific T-cell engagers (BiTEs) of chimeric antigen receptor (CAR) T cells can eliminate residual chemotherapy-resistant B-ALL cells. Objective. The objective of the manuscript is to present improvements in the clinical outcome for chemotherapy-resistant ALL in the real-life setting. Methods. We present the role of novel therapies for relapsed B-cell ALL, including the drugs under investigation in phase I-III clinical trials, as a potential bridge to transplant. Blinatumomab is presented in a critical review, presenting both the advantages of this drug, as well as its limitations. Results. Bispecific antibodies are discussed, describing the clinical trials that resulted in its approval by the FDA and EMA. The real-life setting for relapsed B-cell ALL is described. Conclusion. In the current manuscript, we present blinatumomab as a therapeutic alternative in the bridge-to-transplant setting for refractory or relapsed ALL, to gain a better understanding of the available therapies and evidence-based data for these patients in 2020.